2016
DOI: 10.1021/acscentsci.6b00277
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemistry: A Force of Synthesis

Abstract: The past decade has seen a reawakening of solid-state approaches to chemical synthesis, driven by the search for new, cleaner synthetic methodologies. Mechanochemistry, i.e., chemical transformations initiated or sustained by mechanical force, has been advancing particularly rapidly, from a laboratory curiosity to a widely applicable technique that not only enables a cleaner route to chemical transformations but offers completely new opportunities in making and screening for molecules and materials. This Outlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
641
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,058 publications
(652 citation statements)
references
References 116 publications
4
641
0
7
Order By: Relevance
“…Due to the collision of milling balls inside a planetary ball mill, mechanical energies can be utilized to easily break and build chemical bonds [27]. Moreover, mechanochemistry has been shown to enable unexpected reactions, like the dimerization of fullerenes [28].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the collision of milling balls inside a planetary ball mill, mechanical energies can be utilized to easily break and build chemical bonds [27]. Moreover, mechanochemistry has been shown to enable unexpected reactions, like the dimerization of fullerenes [28].…”
Section: Introductionmentioning
confidence: 99%
“…The key advantages of grinding strategy over conventional approaches include its green [5], safe, simple, solvent-free conditions, as well as its facile work-up, high yield economy and environmental friendliness. Single crystal X-ray study identified the stereo-chemical structure of 2C, which can be also considered as a guide for the prepared derivatives.…”
Section: Conculsionmentioning
confidence: 99%
“…Recently, mechanochemistry offers a cleaner, more efficient alternative to a majority of conventional transformations [5], however, mechano heterocyclic chemistry (MHC) [5,6] draws the attention of heterocyclic chemists towards the uses of grindstone technique in green efficient synthesis of many heterocyclic systems [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is a low cost and green chemistry method employed in the pharmaceutical industry to obtain new solid phases of APIs such as cocrystals, salts, solvates and polymorphs. Solvent assisted grinding is a commonly used mechanochemical method to obtain solid new solid forms of APIs, and the advantages of this method are that it does not depend on the solubility of the compounds and the time reduction in the synthesis process [18][19][20].…”
Section: Introductionmentioning
confidence: 99%